Antibacterial Activity Of Lime Peel (Citrus Aurantifolia (Christm.) Swingle) Ethanolic Extract Against Skin Infection Bacteria (Propionibacterium Acnes And Staphylococcus Epidermidis) - Sormin, Novia; Arianto, Anayanti; Pandapotan, M. (International Journal of Science, Technology & Management, 2023)
The skin is the outermost part of the body that serves as a protective body. In addition to protecting the skin of the face, it also acts as a beautifier. The main problem with facial skin is inflammation of the skin, which can cause acne. Bacteria like Propionibacterium acnes, Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa can cause acne on the face. Prolonged use of antibiotics as therapy against acne will cause a new problem, namely resistance to antibiotics. Lime peel has many uses, especially as an antibacterial, which makes it a good candidate for use as an antibacterial agent in acne treatment. The goal of this study was to find out if the etTMhanolic extract of lime peel could kill bacteria like Propionibacterium acnes and Staphylococcus epidermidis. The research method used the Kirby-Bauer method and the Streaking methods to analyze the minimum inhibitory concentration and minimum bactericidal concentration. The results showed MIC at a concentration of 1 mg/mL for each bacterium, while MBC at a concentration of 40 mg/mL in Propionibacterium acnes and 50 mg/mL in Staphylococcus epidermidis. The conclusion is that the extract of lime peel in ethanol can kill bacteria.